Economic Reform in Hungary Since 1968 - Somogyi, Janos; Boote, Anthony (Washington, D.C. : International Monetary Fund, 1991)
This paper examines Hungary's reforms since 1968. It discusses the government's medium-term adjustment program, unveiled in the fall of 1990, which aims to install the key elements of a market economy in three years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet